Higher Tolerance of Canopy-Forming Potamogeton crispus Than Rosette-Forming Vallisneria natans to High Nitrogen Concentration as Evidenced From Experiments in 10 Ponds With Contrasting Nitrogen Levels - Yu, Qing; Wang, Hong-Zhu; Xu, Chi; Li, Yan; Ma, Shuo-Nan; Liang, Xiao-Min; Jeppesen, Erik; Wang, Hai-Jun (Frontiers in Plant Science, 2018)
Due to excess nutrient loading, loss of submersed macrophytes is a worldwide phenomenon in shallow lakes. Phosphorus is known to contribute significantly to macrophyte recession, but the role of nitrogen has received increasing attention. Our understanding of how high nitrogen concentrations affect the growth of submersed macrophytes, particularly under natural conditions, is still limited. In this study, we conducted experiments with canopy-forming Potamogeton crispus in 10 ponds subjected to substantial differences in nitrogen loading (five targeted total nitrogen concentrations: control, 2, 10, 20, and 100 mg L-1) and compared the results with those of our earlier published experiments with rosette-forming Vallisneria natans performed 1 year before. Canopy-forming P. crispus was more tolerant than rosette-forming V. natans to exposure to high NH4 concentrations. This is probably because canopy-forming species reach the water surface where there is sufficient light for production of carbohydrates, thereby allowing the plants to partly overcome high NH4 stress. Both the canopy-forming P. crispus and the rosette-forming V. natans showed clear declining trends with increasing chlorophyll a in the water. Accordingly, shading by phytoplankton might be of key importance for the decline in submersed macrophytes in this experiment. Both experiments revealed free amino acids (FAA) to be a useful indicator of physiological stress by high ammonium but is not a reliable indicator of macrophyte growth.